Upaya Meningkatkan Kemampuan Pemahaman Konsep Matematis Peserta Didik melalui Model Pembelajaran Problem Based Learning di Kelas VIII SMP Negeri 3 Siduaori - Budi Hati Ndruru (Departement of Mathematics Education, 2024)
This Classroom Action Research (PTK) was motivated by students' lack of understanding of mathematical concepts in mathematics education subjects. Therefore, this Classroom Action Research (PTK) aims to describe how to improve students' ability to understand mathematical concepts through the problem based learning model in Class VIII of SMP Negeri 3 Siduaori. This type of research is Classroom Action Research (PTK) which consists of 2 cycles. The subjects in this classroom action research (PTK) were Class VIII students at SMP Negeri 3 Siduaori with a total of 20 students. The results of the research showed that in the first cycle, the results of the test scores on students' ability to understand mathematical concepts showed that of the 20 students who were research subjects, there were 13 or 65% who got a score in the poor category, and 7 students or 35% who got The value is in the good category. This means, after implementing the problem based learning model, the ability to understand mathematical concepts of class VIII students at SMP Negeri 3 Siduaori in cycle I has increased but has not yet reached completeness. Therefore, researchers continued research in cycle II. The test scores for the ability to understand students' mathematical concepts obtained in cycle II, namely 20 students who were research subjects, showed that 100% of students achieved completeness with an average score of 86.5. This shows that the application of the problem based learning model with the improvements made after implementing cycle I has experienced significant improvement and has reached completion. In this case, the problem based learning model can improve students' ability to understand mathematical concepts in learning mathematics on the subject of circles in class VIII of SMP Negeri 3 Siduaori.